Complex Formation in a Liquid-Liquid Extraction System Containing Cobalt(II), 4-(2-Pyridylazo)resorcinol, and Nitron. (21st March 2013) - Racheva, Petya Vassileva; Gavazov, Kiril Blazhev; Lekova, Vanya Dimitrova; Dimitrov, Atanas Nikolov
Abstract : Complex formation and liquid-liquid extraction were studied in a system containing cobalt(II), 4-(2-pyridylazo)resorcinol (PAR), 1, 4-diphenyl-3-(phenylamino)-1H-1, 2, 4-triazole (Nitron, Nt), water, and chloroform. The effect of some experimental parameters (pH, shaking time, concentration of PAR, and concentration of Nt) was systematically investigated, and the optimum conditions for cobalt extraction as an ion-association complex, (NtH + )[Co 3+ (PAR)2 ], were found. The following key equilibrium constants were calculated: constant of association ( Log β = 4.77 ± 0.06 ), constant of distribution ( Log K D = 1.34 ± 0.01 ), and constant of extraction ( Log K ex = 6.11 ± 0.07 ) . Beer's law was obeyed for Co concentrations up to 1.7  μ g mL −1 with a molar absorptivity of 6.0 × 10 4 L mol −1  cm −1 at λ max = 520  nm. Some additional characteristics, such as limit of detection, limit of quantification, and Sandell's sensitivity, were estimated as well.